2020
DOI: 10.1128/aac.02192-19
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-Mediated Oxygen Enrichment Eradicates Helicobacter pylori In Vitro and In Vivo

Abstract: Helicobacter pylori is an important risk factor for gastric ulcers. However, antibacterial therapies increase the resistance rate and decrease the eradication rate of H. pylori. Inspired by the microaerophilic characteristics of H. pylori, we aimed at effectively establishing an oxygen-enriched environment to eradicate and prevent the recurrence of H. pylori. The effect and the mechanism of an oxygen-enriched environment in eradicating H. pylori and preventing the recurrence were explored in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Mongolian gerbils are small rodents that develop similar infection symptoms, such as appetite and weight loss, and recapitulate many features of H. pylori -induced gastric colonization, inflammation, ulceration, and carcinogenesis, as seen in humans [ 23 , 24 , 25 , 26 , 27 ]. Several other studies demonstrated the development of H. pylori -induced gastric ulcers, duodenal ulcers, and IM following an experimental bacterial challenge in Mongolian gerbils [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mongolian gerbils are small rodents that develop similar infection symptoms, such as appetite and weight loss, and recapitulate many features of H. pylori -induced gastric colonization, inflammation, ulceration, and carcinogenesis, as seen in humans [ 23 , 24 , 25 , 26 , 27 ]. Several other studies demonstrated the development of H. pylori -induced gastric ulcers, duodenal ulcers, and IM following an experimental bacterial challenge in Mongolian gerbils [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Moreover, the bacterial counts of H. pylori in the triple-drug group were higher than those in the hydrogen peroxide group and lower than those in the H. pylori -infected control group. Overall, the results of this study indicated a higher efficacy of hydrogen peroxide in eliminating and preventing the recurrence of H. pylori than that of triple-drug therapy [ 23 ]. Moreover, the study found no toxicity or damage due to hydrogen peroxide in the gastric mucosa.…”
Section: Animal Models To Evaluate Therapeutics Against H P...mentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of low concentrations od hydrogen peroxide in cooked carrots does not appear to raise health problems and may even have beneficial effects. Hydrogen peroxide can exert bactericidal and virucidal action contributing to the mouth hygiene and health (Hernandez et al 2019, Caruso et al 2020) and acting on Helicobacter pylori in the stomach (Di et al 2020). This compound promotes gastric motility (Fajardo et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The sheep blood supplement allows the culture of most culturable bacteria, regardless of their metabolic requirements 1 . Columbia blood agar has been used to cultivate bacteria from different animal taxa including birds (Ruiz-de-Castañeda et al, 2011b;Merbach et al, 2019) and mammals (Infante et al, 2008;Di et al, 2020).…”
Section: Bacteria Sampling and Cultivation Proceduresmentioning
confidence: 99%